Fiscal frameworks in the 21st century. Critical discussion of fiscal policy and private sector development in the recent history of Ukraine, 1991-2024 - Мединська Тетяна Володимирівна; Vasyl Holovachko; Mariana Vykliuk; Maksym Vovk (Ediciones Clío, 2025)
Within the parameters of descriptive methodology based on data from documentary sources, the objective of this research was to analyze fiscal frameworks in the 21st century with a critical focus on fiscal policy and private sector development in Ukraine between 1991 and 2024. This analysis covers the different historical stages of the country: from its independence in 1991, to its current struggle to maintain national sovereignty. From this objective, three key questions emerge that this article sought to answer in its development: How have fiscal frameworks evolved in Ukraine since independence? What impact has fiscal policy had on private sector development? And what historical lessons can be drawn for other countries facing similar crises? The results obtained lead to the conclusion that, the strategic need for a just peace for Ukraine is evident from a fiscal and economic perspective, as no fiscal framework, no matter how sophisticated, can compensate for the devastating effects of a protracted war. The peace negotiations will operate under complex geopolitical interests, where external actors such as the European Union, the United States and international financial organizations will play a determining role, not only in diplomatic but also in economic terms.
Clio. Journal of History, Human Sciences and Criti-cal Thought, 2025 (11), p. 31-58.
Keywords: fiscal policy; contemporary history of Ukraine; critical thinking; private sector; economic entity; taxing policy